The electrical properties of a sandwich of electrodeposited polypyrrole nanofibers between two layers of reduced graphene oxide nanosheets - Mahmoudian, M.R.; Alias, Yatimah; Basirun, Wan Jefrey (Elsevier, 2012)
A sandwich of polypyrrole (PPy) nanofibers between two electrodeposited reduced graphene oxide (RGO) layers was prepared by an electrochemical method. The structure and compositions were characterised by field emission scanning electron microscopy (FESEM) and Fourier transform infrared (FT-IR) spectroscopy. The electrical properties were studied by electrochemical impedance spectroscopy (EIS). The FESEM results confirmed synthesis of a sandwich structure with PPy nanofibers between two electrodeposited RGO layers (RGO/PPy/RGO). The mean width of PPy nanofibers was approximately 76 +/- 16 nm. The EIS results showed that the charge transfer resistance of the coated glassy carbon electrode (GCE) with a sandwich structure of RGO/PPy/RGO was significantly decreased in comparison with coated GCE with PPy nanofibers. This was because the RGO with many small band gaps is more favourable for electron conduction. The comparison of EIS results shows that diffusion of active species through the RGO layers is increased in the presence of the second layer of RGO. The simulation results indicate a high interfacial capacitance (C-dl) of 2170.60 mu F cm(-2) for the coated GCE with RGO/PPy/RGO compared with 360.77 mu F cm(-2) for coated GCE with PPy/RGO. This difference in capacitance can be attributed to the highly accessible specific surface area of graphene and its high efficiency towards electrolyte ion absorption. (C) 2012 Elsevier Ltd. All rights reserved.